Building Sustainability of the Servqual Gap System with the 5 Dimensional Model of Physical Evidence - Alifah Nur Astari; Johan Alfian Pradama (Journal of Advanced Industrial Technology and Application, 2024)
The digital era demands increasingly better quality computerized education services. However, a robust service quality measurement system, especially for the physical evidence dimension, still does not exist. The current system lacks precision, efficiency and effectiveness in measuring physical evidence. This results in organizations not having sufficient information to improve service efficiency, identify areas that need improvement, and optimize resources. This research develops a more sophisticated, accurate and efficient service quality measurement system for the tangible dimension by integrating Simulink and Fuzzy Logic. This research uses a mixed method with a quantitative and qualitative design. The research sample consisted of 100 respondents. Data was collected via e-questionnaire and analyzed using Simulink and Mamdani’s Fuzzy Logic Designer. This research develops a sophisticated, accurate and efficient tangible dimension service quality measurement system. This system uses Simulink and Fuzzy Logic Mamdani. The results show that customers are quite satisfied with the tangible aspects. Fuzservqual shows a value of 3.00 - 3.76 for all tangible attributes, including the "fairly satisfied" category. Simulink and Fuzzy Logic Mamdani produce almost the same Fuzservqual results. This integration offers an accurate, efficient and effective measurement system. This helps improve the overall quality of service. These advantages help organizations improve measurement efficiency and effectiveness, identify areas that need improvement, optimize resources, increase customer satisfaction, save time and costs, increase measurement accuracy and reliability, facilitate collaboration and system development, adapt the system to various types of services and contexts , and meet the specific needs of the organization.